PENGARUH DESENTRALISASI FISKAL DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI PROVINSI DI PULAU SUMATERA - Taufik Rahman (Jurusan Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis, Universitas Lampung, 2018)
Fiscal decentralization and economic growth are the two main issues that continue to be discussed. Both of these topics are not resolved in view of the important relationship between the two. The relationship is more specifically examined in the economic sphere of whether fiscal decentralization has a positive or negative effect on economic growth. Indeed, from various studies on fiscal decentralization and economic growth that have been done before there are different results. This study aims to analyze the effect of fiscal decentralization and labor on the economic growth of the province on the island of Sumatra partially and wholly. The data used in the study is secondary data for the period 2011-2015. Hypothesis testing is done by Data Panel Regression Analysis method by using Eviews 9.0 program to analyze the influence of Fiscal Decentralization and Labor on Economic Growth Province in Sumatera Island. The test used is chow test, hausman test, t test and F test. The result of data analysis shows that Fiscal Decentralization of Expenditure side, Fiscal Decentralization of Revenue and Labor side have positive and significant influence to Economic Growth Province in Sumatera Island. Partially, Fiscal Decentralization of Expenditure and Labor Affects Positive and Significant Effect on Economic Growth of Province in Sumatera Island. While Decentralization of Revenue side have positive but not significant influence to Economic Growth Province in Sumatera Island.